Tingkat Pengetahuan ASI Eksklusif pada Ibu Primipara di Dusun Pundong Kelurahan Srihardono Kecamatan Pundong Kabupaten Bantul - Endah Puji Astuti; Fara Adhiba (LPPM STIKES Guna Bangsa, 2017)
Background : Exclusive breastfeeding is the infant only breastmilk alone were given no food or liquid other than drugs, vitamins, and minerals. Primiparous mothers lack of knowledge about exclusive breastfeeding is good general, the definition of breastfeeding, benefit of breastfeeding, composition of breastfeeding, and how breastfeeding may be influenced by several factor, such as age, education, work, and resources, so that it can directly affect the success of exclusive breasfeeding. Objective : determine the level of knowledge of exclusive breastfeeding in primipara mothers. Methods : this research used descriptive method. Sampling by using total sampling. A large sample of 60 respondent. Analysis using descriptive. Result : based on the result of the research, found most respondent are mother with less knowledge of exclusive breastfeeding, as many as 36 respondents (60,0%). Primiparous mothers with the level of knowledge about the definition of breastfeeding exclusive less category as much as 41 respondents (68,3%). Primiparous mothers with the level of knowledge about the benefits of breastfeeding exclusive good category as much as 32 respondents (53,3%). Primiparous mothers with the level of knowledge about the composition of breastfeeding exclusive enough category as much as 33 respondents (55,0%). Primiparous mothers with the level of knowledge about how breastfeeding may be influenced exclusive less category as much as 40 respondents (66,7%). Conclusion : in this study indicate the level of knowledge of mothers who are less due to maternal characteristic ( occupation and resources), and therefore can be expected in health personel actively provide counseling on exclusive breastfeeding.